Gender, Age and Context in the Use of Sex-Related Verbal Taboos in Traditional Igbo Society - Ihemamma Uwazuruonye Osonwa (RIRAI Publisher, 2024)
The study investigated how gender and age disparities, and situation/ context shape the use of sex-related verbal taboos. It adopted the qualitative orientation which involved semi-structured interviews with a total of 20 participants drawn from four purposively chosen communities or Igbo areas namely, Edda/Afikpo, Owerri, Uzuakoli and Awka. It was framed around the taboo theory of gender differences. The study identified some terms relating to sex and other parts of the body which constitute verbal taboo, and highlighted how gender and age disparities, as well as contexts shape the use of the verbal taboos. It also observed more female restrictive use of the taboo terms/expressions than male which speaks to the culture of patriarchy. Varied contexts or situations of use of the taboo terms were identified including ‘closed’ and ‘open’ contexts. It was concluded that gender and age disparities as a feature of verbal taboos depend on the culture and their underlying beliefs and values.